FEATURES OF CONFUSING PHRASES IN OUR LANGUAGE - Abdujalilova, Feruza (FILOLOGIYA UFQLARI JURNALI, 2024)
This article discusses confusing phrases and their features in our language. Phraseological confusion is analyzed in its original and figurative sense. We have tried to find and analyze examples of these phraseologies from works of art.